THEORETICAL ISSUES OF FORMATION OF MORAL VALUES OF STUDENT YOUTH IN THE REALITIES OF TODAY - Stanislav V. Sapozhnykov; Dovev Mark (Alfred Nobel University Publisher, 2021)
The article analyzes scientific research on the issue of forming the moral values of student youth in today's realities through the prism of Ukraine's European integration aspirations, proves the need for its comprehensive study due to the identified contradictions. The publication thoroughly explores the concepts of "value", "morality", "moral values". Thus, the concept of "value" is analyzed through the prism of philosophical approaches. The above concept is also studied from the point of view of psychology, sociology and pedagogy. The authors define the main functions of morality, thoroughly analyze the concept of "moral values", which is also considered from the standpoint of sociology, psychology and pedagogy. The article provides the author's definition of the process of formation of moral values of student youth, which is considered as a process of rationing based on the internalization of primary values and goals by young people. The authors argue that the formation of moral values of student youth is a systemic process of development and self-development of the individual, and moral education is an integral part of education, which provides a relatively meaningful and purposeful cultivation in accordance with the specific goals, groups and organizations. The publication proves that the main focus of the teacher should be the formation of moral values, and the main goal - the development of the child's personality, capable of conscious and responsible choice of behavior and actions in various life situations, without violating universal values. The article identifies the following main theoretical problems of formation of moral values of student youth: the problem of coordination of teachers and parents educational influences on student youth in the process of their socialization and individualization; filling the methods of formation of educational activities with appropriate moral content; functioning of interrelation and mutual influence of personal qualities of student's youth which are in a stage of their formation; creation of an effective model of formation of moral values of student youth which will consider the sequence of development of various qualities of a person. The paper argues that the formation of moral values of student youth is not a common goal that can be achieved in a certain period of time by specific means. The result of this process should be the formed morality of the individual, which can be defined as the highest goal, which allows the existence of all other goals and is the basis of human activity itself. Thus, the formed morality of student youth can be considered not as a goal, but as an ideal - a regulatory principle and a scale for assessing their behavior.